Comunicação, consumo e educação: o caso da telenovela Amor e Revolução - Araujo, Dayse Maciel de (2013)
The subject of this thesis, related to the axes of communication, cultural consumption and formal / non-formal education, has used, as the object of study, fictional narratives and testimonies of real characters that were part of the TV Novel Amor e Revolução (Love and Revolution). The most popular media product in Brazil, produced by a low reputation broadcasting company in the area of tele-fiction/TV Novels, represented an innovation in plots, as it transmitted, in clear language, the torture and killing of opponents of the civil and military coup d état in 1964. These fictional narratives, which described the repression and resistance of those who opposed the military government, accompanied by the oral stories of the announcers through testimonies, contributed to producing meaning for audience in the context of reinterpretation of our political and social history. Moving the spheres of memory, subjectivity, cultural consumption and non-formal education based on tele-dramaturgy, this study investigated values and meaning for the interface between communication and education. A qualitative approach was used, and to analyze discourse, we based ourselves on the theoretical foundations of French Discourse Analysis. By analyzing the ideological threads of the audiovisual narratives, we see that the reintroduction of recent events in our country by a sociocultural TV Novel, has brought meaning that goes far beyond simple entertainment, since, in some way, it awakened reflection and criticism in the exercise of civic involvement of those who watched Amor e Revolução on TV or on the internet.